Sustainability Report and Financial Performance - Purwasih, Desy; Handayani, Asih (Universitas Pamulang, 2022)
environmental performance in the sustainability report and social performance in the sustainability report on the financial performance of mining companies in the coal sub-sector for the 2018-2020 period. The population in this study were 35 companies. The sample selection in this study used a purposive sampling technique, in order to obtain 14 companies that fit into the criteria. The data analysis technique used is panel data regression using EViews 9.0 software. The results of this study indicate that economic performance in the sustainability report, environmental performance in the sustainability report and social performance in the sustainability report together have an effect on financial performance, economic performance in the sustainability report and environmental performance in the sustainability report have no partial effect on financial performance. While social performance in the sustainability report has a partial influence on financial performance.